(untitled) (Az-Zaida: Jurnal Ilmu Multidisiplin, 2026)
Digital learning media are widely adopted, yet a systematic synthesis of their effectiveness through a balanced examination of advantages and limitations remains lacking. This study addresses this gap by asking: What are the dominant thematic patterns describing the advantages of digital learning media? What themes represent their key limitations? And how does the interplay between these advantages and limitations shape their actual effectiveness in practice? Through a qualitative thematic analysis of literature from Google Scholar, Garuda, and Sinta (2014–2024), the findings identify three core advantage themes enhanced engagement via gamification, expanded accessibility and flexibility, and adaptive personalization and three limitation themes the digital divide that deepens inequality, insufficient teacher pedagogical readiness, and cognitive, socio-emotional, and data-security concerns. The results underscore that effectiveness is not inherent to the technology but emerges from the dynamic interaction between these competing themes within specific educational contexts.